Penerapan Unsur Budaya Indonesia pada Aplikasi Game Tetris Nusantara Berbasis Android - Albertus Agung; Gredion Prajena; Gunawan Gunawan; Ervia Mariski (Bina Nusantara University, 2014)
Game Application of Tetris Nusantara is a game application that can run on mobile devices that have Android operating system. The game has elements of Indonesian culture and a new gameplay of Tetris. Therefore, this game application aims to entertain and introduce cultural diversity that exists in Indonesia so that players are not only entertained but get the knowledge through the application of this ‘Tetris Nusantara’ game. Research methods used in developing applications of this game is the waterfall method of research because it has a stage suitable for developing applications of this game. This game application allows users to find out information about the culture in Indonesia and entertained with a new gameplay of Tetris game. The results of this research is the creation of the archipelago Tetris game application using Indonesian cultural elements that can create interest for players to learn and add to the knowledge of the culture in Indonesia.